Power System Frequency Measurements and Requirements: Assessing the Needs in the Nordic Power System Evaluating Frequency Constraints and Refining Normal Frequency Range for the Future Nordic Power System - Hapuarachchi, Diyasha Chenali (My University, 2025)
Abstract The Nordic power system is undergoing a major transition, with large-scale renewable energy development expected over the next decades. The increasing share of inverter-based generation, higher production variability, and reduced system inertia will affect the frequency stability of the future Nordic grid. The aim of this thesis is to study frequency measurement methods, frequency sensitive components, and expected frequency variability under normal operating conditions of the future Nordic power system. Higher renewable penetration, with inverter-based connections introduces new challenges such as increased resonance and frequency variability, which increases the need of novel frequency measurement approaches. This study discusses these needs and commercial products such as relays, PMUs and controllers, that use different frequency measurement methods. The review of existing frequency measurement methods highlights various drawbacks of accuracy, signal quality and hardware implementation. Sensitive power system components for frequency such as generators, turbines, transformers, load side equipment, have also been discussed with a focus on the normal operational limits. A frequency variability study was conducted for the future Nordic power system based on the PSSE Nordic 44 model. The original Nordic 44 model was updated to reflect the current Nordic system and two simulation cases were developed considering operational snapshots for a winter day and a summer day. The frequency dynamic behavior was validated using actual frequency measurements. Then, two future scenarios for summer and winter were developed and the future system frequency variability was analysed by applying time series load changes. The results show that the frequency deviation from 50Hz increases with a greater variation in load. Increasing deviation rates are especially observed below 50Hz. Also, the summer day scenario showed a higher frequency fluctuation beyond the normal operational frequency limits compared to the winter day scenario. Future scenarios also showed higher frequency ramping compared to the present system model due to reduced overall system inertia. The findings indicate that the future Nordic power system will experience greater normal frequency variability with greater deviations and frequency ramps. Understanding system changes, being aware of sensitive components, adapting operational standards, and implementing novel frequency measurements to accommodate these changes will be crucial to maintaining system stability.
Keywords: Keywords: Nordic power system, Inverter-based generation, Frequency variability, PSSE Nordic 44 model, System inertia, Normal operational frequency.